Self Acceptance in Stay at Home and Orphanage Teens - Maria Erisvita Lingsiani Sang; Marylin S Junias; Dian Lestari Anakaka (Universitas Nusa Cendana, 2022)
Self-acceptance is the attitude of the individual feeling satisfied with himself and adjusting fully, and unconditionally to accepting himself. Adolescents need family support in the formation of self-acceptance. This study aims to determine the picture of self-acceptance in adolescents who live at home and who live in the Sonaf Maneka Orphanage, Lasiana Village. The approach used is a quantitative approach with a descriptive type of research. The data collection technique used a self-acceptance scale with the results of a measuring instrument trial using a Cronbach Alpha Scale value of 0.633. The respondents to this study were teenagers aged 15-20 years totaling 48 teenagers living in Lasiana village. The results of the study found that self-acceptance in adolescents living at home and living in orphanages was in the moderate category. However, based on the age of adolescents living in nursing homes, the age range is 15-16 years, with 4 respondents (8.3%).